PENERAPAN METODE EXAMPLE NON EXAMPLE DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL DALAM MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR SISWA KELAS VII.1 MTSN BINTUHAN - arda megawati (UIN Fatmawati Sukarno Bengkulu, 2017)
Abstract: This study uses data collection techniques by observation, achievement test, and dokumentsi and data analysis techniques, from the data collected at each observation of the implementation cycle of PTK, analyzed descriptively using percentages techniques to see trends occurring in the learning activities. then the data is classified into two groups, namely quantitative and qualitative data. From the results of classroom action research carried out in three cycles of this, it can be concluded that the application of the method of example non example using audiovisual media in teaching moral theology can improve student learning activities, on the subjects of moral theology graders VII.1 MTs Bintuhan Subdistrict South Kaur Kaur regency. It is located on the observation data analysis of student learning activity with good criteria. And based on the test results of students in the first cycle of the average value of 60.61 students and the percentage of students in classical learning completeness 30.30% with criteria yet complete, then the second cycle average of 65.61 and the percentage of students learning completeness students 69.70% classical criteria unresolved increased in the third cycle with the average value of students to 70 and the percentage in the classical learning completeness 100% with completion criteria.